Need equation
Cj,
First let's change the variable name "o" to "B" because sooner or later "o" will get mixed up with "0", zero!
A votes: Va
B votes: Vb
Va= Vb - 47628
Therefore Vb = Va + 47628
And B won the election! ;-)
BruceS
Need equation
Cj,
First let's change the variable name "o" to "B" because sooner or later "o" will get mixed up with "0", zero!
A votes: Va
B votes: Vb
Va= Vb - 47628
Therefore Vb = Va + 47628
And B won the election! ;-)
BruceS
If I am reading your post right and there is no more to the problem:
A = O - 47628
Key phrase here is "votes less then" meaning taking it away from.
It wants you to solve for O so you add 47628 to A to get O
O = A + 47628
Comments
More information is needed such as the percentage of votes A obtained (or something like that).